Fere Kie and Kololi Kie: A Study of the Relationship between Religion, Culture and Nature in Ternate Ethnic Communities as an Environmental Resilience Effort - Fatah, Rahmat Abd; Suleman, Syukur; Gamlamo, Elsa Grace; Umarama, Rahmat (Technium Social Sciences Journal, 2024)
The form of tradition of a place is an expression of the soul of its people, in which there are various meanings and encounters of culture, religion and the environment in which the community is located, including the tradition of Fere Kie (Up the Mountain) and Kololi Kie (Around the Mountain) in Ternate as a form of relationship between religion and culture. Thus the purpose of this research is to reveal the meaning of the two traditions using qualitative methods and phenomenology. While the theoretical approach as an analytical tool is Max Weber’s social action theory and Peter L. Berger’s Social Construction used to construct the social actions of the community in maintaining the balance of nature and humans as local wisdom-based environmental resilience. The results of the study revealed the meaning of the Fere Kie and Kololi Kie traditions as First, the soul of the Sufistic Spiritualism of the Ternate people. Second, as the identity of the religious culture of the Ternate people, and Third, as a transformation of environmental ethics. Therefore, the research found that the relationship between religion, culture and nature becomes a cosmological unity in the Fere Kie and Kololi Kie traditions in Ternate, which potentially can be used culturally to create environmental ethics as an effort to resilience the local environment.